2018
DOI: 10.1007/s00277-017-3214-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel heterozygous ITGB3 p.T720del inducing spontaneous activation of integrin αIIbβ3 in autosomal dominant macrothrombocytopenia with aggregation dysfunction

Abstract: We identified a novel heterozygous ITGB3 p.T720del mutation in a pedigree with macrothrombocytopenia exhibiting aggregation dysfunction. Platelet aggregation induced by ADP and collagen was significantly reduced, while ristocetin aggregation was normal. Integrin αIIbβ3 was partially activated in a resting status, but platelet expression of αIIbβ3 was downregulated. Functional analysis using a cell line showed spontaneous phosphorylation of FAK in αIIb/β3 (p.T720del)-transfected 293T cells in suspension conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Mutations in this region lead to constitutive activation of αIIbβ3 and induce aberrant outside‐in signaling via αIIbβ3 . Recent genetic studies on congenital macrothrombocytopenia suggest that gain‐of‐function mutations of αIIbβ3 in this region may affect not only platelet function but also platelet counts and morphology, which is referred to as αIIbβ3 ( ITGA2B/ITGB3 )‐related macrothrombocytopenia . In the present study, we showed that the αIIb(R990W) mutation in mice corresponding to αIIb(R995W) in humans, which is the most prevalent mutation in αIIbβ3‐related thrombocytopenia in Japan, induces mild thrombocytopenia with enlarged platelet size and downregulation of αIIbβ3 expression in platelets, leading to GT‐like severe platelet dysfunction in homo mice.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Mutations in this region lead to constitutive activation of αIIbβ3 and induce aberrant outside‐in signaling via αIIbβ3 . Recent genetic studies on congenital macrothrombocytopenia suggest that gain‐of‐function mutations of αIIbβ3 in this region may affect not only platelet function but also platelet counts and morphology, which is referred to as αIIbβ3 ( ITGA2B/ITGB3 )‐related macrothrombocytopenia . In the present study, we showed that the αIIb(R990W) mutation in mice corresponding to αIIb(R995W) in humans, which is the most prevalent mutation in αIIbβ3‐related thrombocytopenia in Japan, induces mild thrombocytopenia with enlarged platelet size and downregulation of αIIbβ3 expression in platelets, leading to GT‐like severe platelet dysfunction in homo mice.…”
Section: Discussionsupporting
confidence: 51%
“…Abnormal proplatelet formation was observed in constitutively active αIIbβ3‐transduced megakaryocytes, as well as megakaryocytes obtained from patients with αIIbβ3‐related macrothrombocytopenia . Although the precise mechanisms remain to be elucidated, previous studies suggested that constitutive activation of focal adhesion kinase induced by the active form of αIIbβ3 causes abnormal actin remodeling via inhibition of RhoA activation . Furthermore, our results showed that platelet lifespan was slightly but significantly shortened in homo mice (Figure C), which could in turn partially affect thrombocytopenia in KI mice.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations